IMPLEMENTATION OF CHANGE MANAGEMENT IN ORGANIZATIONS DOMINATED BY MECHANICAL BUREAUCRACY - Mihaela BARCAN; Laurentiu BARCAN (Journal of Defense Resources Management, 2021)
Almost two years after the outbreak of the COVID-19 pandemic, the Romanian institutions in the fields of public health and national security have gone through and continue to go through processes of organizational change, with a major impact in terms of national security. Change management in these organizations of military origin is based mainly on coercion, being dependent on the political factor and the mechanistic bureaucracy, the resistance encountered being likely to affect national policies to combat the perpetuation of the pandemic and its effects.